Faktor-Faktor Penyebab Rendahnya Kesadaran Petani dalam Membayar Zakat Pertanian di Desa Pelangkidul, Kecamatan Kedunggalar, Kabupaten Ngawi - Rahmadita, Annisa; Hanifuddin, Iza (Nidhomiya: Research Journal of Islamic Philanthropy and Disaster, 2023)
Awareness is the most important element in fostering a desire in a person especially to pay zakat. When there is no awareness in a person to carry out zakat, it will be difficult to do so. Pelangkidul Village has an area of 410.3 ha of rice fields. With a population of 4,000 people who work as farmers. Looking at this, the potential for agricultural zakat in Pelangkidul Village is also quite large. However, the reality that occurs in rice farming communities related to the potential for zakat payments is still very low. Where this is one of them influenced by public awareness of the implementation of agricultural zakat payments is very less in accordance with existing theories. This study aims to analyze the awareness of rice farmers in Pelangkidul Village in paying agricultural zakat, analyze the factors that cause low awareness of rice farmers in paying agricultural zakat and analyze the impact of low awareness of rice farmers on agricultural zakat payments. The method used in this study is qualitative with the type of field research (field research) which uses data collection techniques in the form of observation, interviews and documentation. The results of this study are that the awareness of rice farmers in Pelangkidul Village is still low because most of the people who work as farmers are only a small proportion who are aware of the obligation to pay agricultural zakat, but with payment practices that are still not in accordance with the provisions in agricultural zakat. They only spend a little of the harvest as a form of gratitude. While others do not pay zakat on agricultural products. The factors that cause low awareness in paying agricultural zakat consist of a lack of public understanding, a lack of public curiosity, a lack of socialization regarding agricultural zakat, educational factors, religiosity factors and the absence of supporting platforms. The low awareness of farmers automatically has an impact on the payment of agricultural zakat, many rice farmers in Pelangkidul Village do not pay zakat for their agricultural products. Even if the rice farmer pays zakat for his agricultural products, the implementation is not in accordance with the provisions in agricultural zakat. Kesadaran merupakan unsur terpenting dalam menumbuhkan keinginan pada diri seseorang terkhusus untuk membayar zakat. Ketika belum ada kesadaran dalam diri seseorang untuk melaksanakan zakat, maka akan terasa berat untuk melakukannya. Desa Pelangkidul memiliki luas wilayah persawahan 410,3 ha. Dengan penduduk yang berprofesi sebagai petani sebanyak 4.000 jiwa. Melirik hal tersebut seharusnya menjadikan potensi zakat pertanian di Desa Pelangkidul juga cukup besar. Namun realita yang terjadi pada masyarakat petani padi terkait potensi pembayaran zakat masih sangat rendah. Dimana hal tersebut salah satunya dipengaruhi oleh kesadaran masyarakat terhadap pelaksanaan pembayaran zakat pertanian sangat kurang sesuai dengan teori yang ada. Penelitian ini bertujuan untuk menganalisis kesadaran petani padi di Desa Pelangkidul dalam membayar zakat pertanian, menganalisis faktor-faktor penyebab rendahnya kesadaran petani padi dalam membayar zakat pertanian serta menganalisis dampak rendahnya kesadaran petani padi pada pembayaran zakat pertanian. Metode yang digunakan dalam penelitian ini adalah kualitatif dengan jenis penelitian lapangan (field research) yang menggunakan teknik pengumpulan data berupa observasi, wawancara dan dokumentasi. Hasil penelitian ini adalah kesadaran petani padi di Desa Pelangkidul tergolong masih rendah karena sebagian besar masyarakat yang berprofesi sebagai petani hanya sebagian kecil yang sadar akan adanya kewajiban membayar zakat pertanian, tetapi dengan praktek pembayaran yang masih belum sesuai dengan ketentuan-ketentuan yang ada pada zakat pertanian. Mereka hanya mengeluarkan sedikit dari perolehan hasil panen sebagai bentuk rasa syukur. Sedangkan sebagian lainnya tidak membayar zakat hasil pertaniannya. Adapun faktor penyebab rendahnya kesadaran dalam membayar zakat pertanian terdiri dari kurangnya pemahaman masyarakat, kurangnya rasa ingin tahu masyarakat, kurangnya sosialisasi terkait zakat pertanian, faktor pendidikan, faktor religiusitas dan tidak adanya wadah pendukung. Rendahnya kesadaran petani secara otomatis berdampak pada pembayaran zakat pertanian, banyak petani padi di Desa Pelangkidul yang tidak membayarkan zakat hasil pertaniannya. Kalaupun petani padi tersebut membayarkan zakat hasil pertaniannya, pelaksanaannya belum sesuai dengan ketentuan yang ada pada zakat pertanian.